Plasmacytoid dendritic cells and their role in the immunopathogenesis of viral infections for example hepatitis B - R. R. Khodzhibekov; O. N. Khokhlova; A. R. Reizis; G. M. Kozhevnikova (Журнал инфектологии, 2019)
A new approach in understanding the mechanisms of immune response in viral hepatitis is the discovery of a unique type of immune cells – plasmocytoid dendritic cells (pDCs). Plasmocytoid dendritic cells (pDCs) are cells of lymphoid origin and morphologically resemble plasma cells. Functionally, they are professional IFN-a-producing cells that play an important role in antiviral immune response. Data on the mechanisms of PDCs participation in hepatitis B virus infection are few and contradictory. In chronic HBV infection, the role of pDCs remains mysterious and poorly understood with conflicting circulating blood pDCs results that show differently that they are not affected or reduced. However, functional disorders of pDCs were observed in patients with chronic HBV infection. The establishment of these mechanisms, as well as the search for the cause of hepatitis B virus latency and the formation of chronic infection remains one of the important and promising areas of scientific activities today.